Realization of Interlinked ZnO Tetrapod Networks for UV Sensor and Room-Temperature Gas Sensor - Meechai Thepnurat (2018)
© 2015 American Chemical Society. Here, interlinked ZnO tetrapod networks (ITN-ZnO) have been realized by using microwave-assisted thermal oxidation. With this simple and fast process, a nanostructured ZnO morphology having tetrapodlike features with leg-to-leg linking is obtained. The electrical and ethanol-sensing properties related to the morphology of ITN-ZnO compared with those of other ZnO morphologies have also been investigated. It has been found that ITN-ZnO unexpectedly exhibits superior electrical and gas-sensing properties in terms of providing pathways for electron transport to the electrode. A UV sensor and a room-temperature gas sensor with improved performance are achieved. Therefore, ITN-ZnO is an attractive morphology of ZnO that is applicable for many new applications because of its novel properties. The novel properties of ITN-ZnO are beneficial for electronic, photonic, optoelectronic, and sensing applications. ITN-ZnO may provide a means to improve the devices based on ITN-ZnO.